2013
DOI: 10.1002/prca.201300074
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of serum/plasma proteins in various infectious diseases: Specific or nonspecific signatures

Abstract: Apart from direct detection of the infecting organisms or biomarker of the pathogen itself, surrogate host markers are also useful for sensitive and early diagnosis of pathogenic infections. Early detection of pathogenic infections, discrimination among closely related diseases with overlapping clinical manifestations, and monitoring of disease progression can be achieved by analyzing blood biomarkers. Therefore, over the last decade large numbers of proteomics studies have been conducted to identify different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 123 publications
2
40
0
Order By: Relevance
“…However, downregulation of Hp peptides in dengue fever samples was not significant as compared to malaria (Figure C). The present MRM findings complemented our previous reported iTRAQ data . The precise trends of all three peptide are displayed in Supporting Information, Figure 1.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, downregulation of Hp peptides in dengue fever samples was not significant as compared to malaria (Figure C). The present MRM findings complemented our previous reported iTRAQ data . The precise trends of all three peptide are displayed in Supporting Information, Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…Previous proteomics studies from our lab showed that levels of haptoglobin were highly dysregulated in severe malaria cases as compared to non‐severe malaria. Hence, haptoglobin was used for the MRM studies, and three unique peptides were screened.…”
Section: Methodsmentioning
confidence: 81%
“…It is important to emphasize that several serum/plasma proteins, particularly those which are associated with acute phase response signaling cascades, frequently exhibit differential abundant in various diseased conditions [8]. Usually such candidates alone cannot be implemented as reliable diagnostic markers for any specific disease or infection in a general population.…”
Section: Discussionmentioning
confidence: 98%
“…Indepth analysis of the differential abundances of serum/plasma proteins during the febrile stage of the infection may help in identification of surrogate markers of infection and disease severity and can provide valuable information regarding disease pathogenesis and host immune responses [8,9]. A few previous studies have investigated the alterations in plasma proteome profiles in cerebral falciparum malaria in children from different endemic and holoendemic regions of Africa [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the fundamental processes moderated by the plasma proteome, such as inflammation and coagulation, are concomitant with a range of health disorders, common markers might be expected between similar or related diseases. Accordingly, the observation of the common proteins markers in different cancers and viral infections has been reported . For example, alpha‐1‐acid glycoprotein 1 (ORM1) has been detected in non‐small cell lung cancer and gastric adenocarcinoma, and apolipoprotein A‐IV (APOA4) in ovarian and pancreatic cancers .…”
Section: Methodsmentioning
confidence: 99%